Dimensi Kecerdasan dalam Doa Qur’aniyyah KH. Mufid Mas’ud - Nurkholis, Ahmad; Mudhofar, Hanif; Imam, Masyayikh (Al Furqan: Jurnal Ilmu Al Quran dan Tafsir, 2024)
This study aims to analyze the exegesis of the Qur'anic prayers practiced by KH. Mufid Mas'ud, focusing on a deep understanding of the meaning of these prayers and their implications for the development of individual intelligence. The study employs a qualitative method and theoretical analysis based on intelligence concepts proposed by Louis Thurstone, Daniel Goleman, Danah Zohar, and Ian Marshall. The research identifies three types of intelligence contained in the Qur'anic prayers of KH. Mufid Mas'ud: intellectual intelligence (IQ), emotional intelligence (EQ), and spiritual intelligence (SQ). The results of the study indicate that the Qur'anic prayers of KH. Mufid Mas'ud play an important role in enhancing an individual's spiritual awareness (SQ), enabling one to deepen the relationship with God and strengthen spiritual values in daily life. From the EQ perspective, these prayers serve as a tool to help individuals manage emotions, provide inner peace, and alleviate emotional stress arising from life difficulties. Meanwhile, from the IQ perspective, although prayer does not directly influence intellectual abilities, the practice of prayer that involves reflection and critical thinking can stimulate cognitive development, improve concentration, and support the pursuit of knowledge. This study concludes that the Qur'anic prayers of KH. Mufid Mas'ud are not only a spiritual medium but also a means for the holistic development of intelligence, encompassing intellectual, emotional, and spiritual dimensions. These findings provide an important contribution to integrative studies that link spirituality with human intelligence, enriching the perspective on understanding the role of prayer in an individual's life.